Alpha-1 Antitrypsin Blood Levels as Indicator for the Efficacy of Cancer Treatment - El-Akawi, Zeyad J. (World J Oncol, 2013)
BACKGROUND: Alpha-1 antitrypsin (α(1)-AT) is a member of the serine protease inhibitors (serpins) family. Liver cells are the major source of synthesis and secretion of (α(1)-AT) into the blood. Moreover, it has been demonstrated that α(1)-AT is expressed and secreted by many types of malignant cells. Studies have indicated that serum levels of (α(1)-AT) increase in a good number of malignant diseases. In addition, a significant correlation between serum levels and cancer stage has also been reported. In this work we aimed to test how α(1)-AT levels behave at the third week after treatment with chemotherapy. METHODS: The α(1)-AT blood levels were measured using commercially available radial immunodiffusion kit (Kent Laboratory Inc, Bellinham, Washigton) following manufacturer instructions. RESULTS: The α(1)-AT blood levels were significantly decreased after treatment compared with those before the treatment started. The mean difference (before - after) treatment was 127.82 and 137.37 mg/dL with 95% CI of difference 109.06 - 146.57 and 116.08 - 158.65 mg/dL in lung and prostate cancer respectively. When we compared these levels according to the stage of cancer, we found that the mean difference (before - after) treatment was also highly significant as indicated by P-value and the 95% CI of these differences. CONCLUSION: Obtained data strongly indicate the value of testing α(1)-AT blood levels as one of the important indicators for the efficacy of cancer treatment.